The Effectiveness of Digital Marketing in Businesses During Pandemic at Novaliches in Quezon City: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Every individual needs to be improved and knowledgeable about digital marketing in business. That means every businessperson and entrepreneur can improve their businesses using digital marketing. Therefore, the researchers chose this topic to help focus on targeted audiences with a global reach, unlike traditional marketing, bringing in high revenue with little investment. So, the purpose is to help the businessperson and entrepreneur with the effectiveness of digital marketing in business, and this study's significance is it will help the businessperson and entrepreneur master their digital marketing skills. The business will benefit because the businessperson or entrepreneur excels in traditional marketing and will be globally competitive through digital marketing. The researchers use descriptive research design, which is The best way way to know and understand the situation or this research. In this Research, the exact behaviour of the respondents is based on the survey, and we can easily know their respective perceptions about the Effectiveness of Digital Marketing.  The study's respondents were 50 student business owners around Novaliches, Quezon City. This study focuses on identifying the barriers to effective digital marketing. Based on the study's results, the effectiveness of digital marketing during the pandemic addressed the above-cited factors and improved marketing in terms of: (1) Social Media Platforms – Business owners choose to sell through social media. (2) Advertising helps business owners grow their sales, especially during the pandemic. The researchers recommend to the students that they should be aware of the use of Digital Marketing because the help of Digital Marketing in business has a big impact on it. It can make many businesses continue making money and provide for their financial needs. Lastly, Future Researchers must conduct more studies on the Efficiency of Digital Marketing during the Pandemic.
Keywords: Efficiency; Digital Marketing; Pandemic